Stereotactic body radiotherapy for the pancreas: a critical review for the medical oncologist - Kim, Samuel K.; Wu, Cheng-Chia; Horowitz, David P. (Journal of Gastrointestinal Oncology; Vol 7, No 3 (June 01, 2016): Journal of Gastrointestinal Oncology, 2015)
With recent advances in imaging modalities and radiation therapy, stereotactic body radiotherapy (SBRT) has allowed for the delivery of high doses of radiation with accuracy and precision. As such, SBRT has generated favorable results in the treatment of several cancers. Although the role of radiation has been controversial for the treatment of pancreatic ductal adenocarcinoma (PDAC) due to rather lackluster results in clinical trials, SBRT may offer improved outcomes, enhance the quality of life, and aid in palliative care settings for PDAC patients. This review delineates the role of SBRT in the treatment of PDAC, presents the defining principles of radiation biology and the radiation oncology work flow, and discusses the prospects of new treatment regimens involving tumor immunology and radiation therapy.